Wood reinvented - Mohamad, Rosfarizan; Yahya, Mohamad Ridzuan; Saad, Wan Zuhainis (Universiti Putra Malaysia Press, 2015)
Lignocellulosic material which comprises lignin, hemicelluloses, and cellulose is a sustainable and renewable resource and it can come from forest and agricultural wastes and urban waste. 75 % of the lignocelluloses are made up of carbohydrates. Polysaccharides are the major cell wall constituents in the plant cell with the total amount up to 80 % of the total weight of the woody material. The simple sugar monomers in the polysaccharides can be converted into lactic acid through enzymatic hydrolysis and fermentation process.